Training on Making Yayasan Financial Reports Based on the Guidelines for Financial Accounting Standards - Devira Liandra (Jurnal PKM Manajemen Bisnis, 2022)
Generally, the foundation's financial reports are made in a simple form, this is in accordance with the existing financial conditions. However, the government has made guidelines regarding lean reporting models. It is intended that financial reports can be useful information for interested parties in making decisions. For this reason, this service activity is carried out, as a form of education's contribution to society. The method of activity is carried out by means of lectures and training. The training participants are financial employees from foundations in the Pamulang area, South Tangerang. The results of this activity are in the form of explanations and provision of training on making standardized foundation financial reports. In this activity, the participants gained knowledge about the basic concepts of accounting and also an understanding of the benefits of standardized financial reports, as well as received training in preparing good financial reports.